Photodynamic therapy in clinical practice - E. V. Filonenko; L. G. Serova (Biomedical Photonics)
The review is on opportunities and possibilities of application of photodynamic therapy in clinical practice. The advantages of this method are the targeting of effect on tumor foci and high efficiency along with low systemic toxicity. The results of the set of recent Russian and foreign clinical trials are represented in the review. The method is successfully used in clinical practice with both radical (for early vulvar, cervical cancer and pre-cancer, central early lung cancer, esophageal and gastric cancer, bladder cancer and other types of malignant tumors), and palliative care (including tumor pleuritis, gastrointestinal tumors and others). Photodynamic therapy delivers results which are not available for other methods of cancer therapy. Thus, photodynamic therapy allows to avoid gross scars (that is very important, for example, in gynecology for treatment of patients of reproductive age with cervical and vulvar cancer), delivers good cosmetic effect for skin tumors, allows minimal trauma for intact tissue surrounding tumor. Photodynamic therapy is also used in other fields of medicine, such as otorhinolaryngology, dermatology, ophthalmology, orthopaedics, for treatment of papilloma virus infection and purulent wounds as antibacterial therapy.